Anxiety and depression among caregivers of hemodialysis patients at the Indonesian national referral hospital (Medical Journal of Indonesia, 2018)
Background: In Indonesia, chronic kidney disease (CKD) is primarily managed by hemodialysis (HD) because limited resources rule out the possibility of renal transplantation. HD patients are commonly accompanied by caregivers. However, most studies have neglected the health of caregivers, who play an important role in the survival of HD patients. This study aimed to determine the proportion of caregivers who suffer from anxiety and depression and the factors involved.Methods: This was a cross-sectional study involving 100 caregivers in the HD unit of Cipto Mangunkusumo Hospital, Jakarta. This study used the hospital anxiety depression scale (HADS) to determine the extent of anxiety and depression among caregivers. All caregivers were asked to fill out the questionnaire without assistance.Results: A total of 28% and 18% of caregivers were found to be anxious and depressed respectively. The caregiver's relationship with the patient, whether the caregiver was being paid or unpaid, the total duration of care, and income were not associated with levels of anxiety and depression. However, the proportion of each 24-hour period spent on care was significantly associated with anxiety (p=0.037) and depression (p=0.015). The time spent on care every 24 hours was also a significant predictor of anxiety (p=<0.001) and depression (p=0.021).Conclusion: One-third of caregivers were found to be anxious and/or depressed. The time spent on care every 24 hours was a strong predictor of both anxiety and depression.